Services for the intelligent building / Nik Ahmad Mazli Nik Mohamad and Abdul Azis Arshat - Nik Mohamad, Nik Ahmad Mazli; Arshat, Abdul Azis (Faculty of Mechanical Engineering, 1992)
The aim of this Project is to study in detail, requirement of certain services for an Intelligent Buildings. The services which shall be taken into account are air - conditioning service, lifting and lighting. Intelligent building concept is new in Malaysia, therefore In doing this project we got into much difficulty in getting relevant information about the services for an Intelligent Building CIBX The IBs concept is not yet enforced by any government agency of Malaysia and shall probably not be the case for many years to come. However in order to optimise on resources, Building owners may introduce such concepts into their properties in order to remain competitive.